2018
DOI: 10.1105/tpc.18.00266
|View full text |Cite
|
Sign up to set email alerts
|

Maize Oxalyl-CoA Decarboxylase1 Degrades Oxalate and Affects the Seed Metabolome and Nutritional Quality

Abstract: The organic acid oxalate occurs in microbes, animals, and plants; however, excessive oxalate accumulation in vivo is toxic to cell growth and decreases the nutritional quality of certain vegetables. However, the enzymes and functions required for oxalate degradation in plants remain largely unknown. Here, we report the cloning of a maize () opaque endosperm mutant that encodes oxalyl-CoA decarboxylase1 (EC4.1.1.8; OCD1). is generally expressed and is specifically induced by oxalate. The mutant seeds contain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 64 publications
3
38
0
1
Order By: Relevance
“…were significantly downregulated in fl3 and smk7;fl3 endosperm. The o5, o11, ocd1, and nkd1 mutants have kernels with an opaque endosperm, which is consistent with the fl3 and smk7;fl3 phenotype (Myers et al, 2011;Yi et al, 2015;Feng et al, 2018;Yang et al, 2018). O7 expression was significantly upregulated in the fl3 and smk7;fl3 endosperm, and o7 also has an opaque endosperm (Wang et al, 2011).…”
Section: Rnapiii Affects Storage Reserve Filling In Maize Kernelsupporting
confidence: 68%
See 1 more Smart Citation
“…were significantly downregulated in fl3 and smk7;fl3 endosperm. The o5, o11, ocd1, and nkd1 mutants have kernels with an opaque endosperm, which is consistent with the fl3 and smk7;fl3 phenotype (Myers et al, 2011;Yi et al, 2015;Feng et al, 2018;Yang et al, 2018). O7 expression was significantly upregulated in the fl3 and smk7;fl3 endosperm, and o7 also has an opaque endosperm (Wang et al, 2011).…”
Section: Rnapiii Affects Storage Reserve Filling In Maize Kernelsupporting
confidence: 68%
“…O7 expression was significantly upregulated in the fl3 and smk7;fl3 endosperm, and o7 also has an opaque endosperm (Wang et al, 2011). Notably, OCD1 acts downstream of O7 and encodes oxalyl-CoA decarboxylase, which catalyzes the breakdown of oxalyl-CoA into formyl-CoA and CO 2 (Yang et al, 2018). We observed that genes involved in oxoacid metabolism were significantly enriched in fl3 DEGs (Fig.…”
Section: Rnapiii Affects Storage Reserve Filling In Maize Kernelmentioning
confidence: 76%
“…Mutations either reducing zein protein synthesis or altering its deposition in PBs also create an opaque phenotype in the mature endosperm. Besides these mutations that directly affect starch and PB synthesis, there are many others that indirectly affect their synthesis and cause an opaque endosperm phenotype 26 28 . Evidence from these studies support the hypothesis that the number of PBs, the organization of zein proteins within them, and their interaction with SGs are essential factors for vitreous endosperm formation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…pCAMBIA1300-35S-GFP vector not containing the ZmMdh4 gene was used as the free GFP control (35S::GFP). The 35S::GFP and 35S::ZmMDH4:GFP constructs were transiently expressed in Nicotiana benthamiana (N. benthamiana) leaves and Arabidopsis mesophyll protoplasts as described by Li et al (2017) and Yang et al (2018). GFP signal was observed and imaged using a confocal microscope (FV1000, Olympus).…”
Section: Subcellular Localization Of Zmmdh4mentioning
confidence: 99%